Design and development of novel bioadhesive niosomal formulation for the transcorneal delivery of anti-infective agent: In-vitro and ex-vivo investigations - Yahaya Zubairu; Lalit Mohan Negi; Zeenat Iqbal; Sushama Talegaonkar (Elsevier, 2015)
Gatifloxacin eye drops are frequently used in eye infections. However such formulations have a major drawback i.e. short duration of action and usually require 4-6 times installations daily. A chitosan coated niosomal formulation of gatifloxain was purposed to show a longer retention time on eyes and subsequent reduction in dosing frequency. Vesicles were prepared by solvent injection method using cholesterol and Span-60. An extensive optimization of formulation was done using different ratios of cholesterol, Span-60 and drug, revealed NS60-5 (cholesterol: span-60 50: 50 and drug content of 20 mg) to be the optimized niosome formulation. NS60-5 had shown a highest entrapment efficiency of 64.9 ± 0.66% with particle size 213.2 ± 1.5 nm and zeta potential −34.7 ± 2.2 mV. Optimized niosomes were also coated with different concentrations of chitosan and evaluated. Permeation studies had revealed that optimized niosomes (86.77 ± 1.31%) had increased the transcorneal permeation of Gatifloxacin more than two fold than simple drug solution (37.19 ± 1.1%). Longer retention potential of the coated niosomes was further verified by fluorescence microscopy. Study revealed that simple dye solution got easily washed out with in 6 h. The uncoated niosomes (NS60-5) showed a longer retention (more than 6 h), which was further enhanced in case of coated niosomes i.e. CNS60-1 (more than 12 h). Antimicrobial studies had shown the better efficacy of CNS60-1 (zone of inhibition) when compared to marketed formulation. The final chitosan formulation was found to have shown better ocular tolerability as demonstrated by corneal hydration test histopathology investigations.